Overview of the Medical Waste Management System by Health Human Resources (SDK) at the Putri Ayu Public Health Center, Jambi City in 2024 - Ainun Afifah; Fajrina Hidayati; Hendra Dhermawan Sitanggang; Dwi Noerjoedianto; Fitria Eka Putri (Journal of International Multidisciplinary Research, 2024)
According to the Jambi City Health Service Profile in 2021-2022, Putri Ayu Health Center is one of the inpatient health centers in Jambi City which is also acontributes the largest amount of medical waste with the amount of waste is 615 kg out of a total of 7804.1 kg of medical waste from health centers in Jambi City, so it has the potential to spread disease if medical waste is not managed properly. This research uses qualitative research methods with a descriptive approach. Data was obtained from 8 informants by conducting in-depth interviews and observations in May 2023 - April 2024 using qualitative research data analysis software. In the input aspect (1) Human Resources in the quantity aspect are sufficient, while the qualifications are not appropriate because they come from general administration. (2) Facilities and infrastructure are not sufficient and if there is damage, goods will be procured and reported to envinronmental health authority. Meanwhile, in the process aspect (3) Sorting is carried out by each waste producing poly unit by labeling the type of waste, date and poly, (4) The container used at the Putri Ayu Public Health Center meets the standards of Minister of Health Regulation Number 18 of 2020 (5) Transportation is carried out more than once every 2 days by PT Anggrek (6). Storage is carried out at TPS with a time span of 2-3 days at the latest. There are still input aspects that do not comply with standards (in the case of this research, namely the quality of human resources) causing disruption to process aspects, such as less than optimal management performance in managing medical waste in the container, transport and storage processes.